Biochemical and physiological changes in Zea mays L. after exposure to the environmental pharmaceutical pollutant carbamazepine. (July 2023) - Mascellani, Anna; Mercl, Filip; Kurhan, Sebnem; Pierdona, Lorenzo; Kudrna, Jiri; Zemanova, Veronika; Hnilicka, Frantisek; Kloucek, Pavel; Tlustos, Pavel; Havlik, Jaroslav
Abstract: The presence of pharmaceuticals in the environment is a matter of great concern. They are consistently found in the environment, raising concerns regarding human exposure through dietary intake. In this study, we observed the effect of the application of carbamazepine at 0.1, 1, 10, and 1000 μg per kg of soil contamination levels to assess stress metabolism in Zea mays L. cv. Ronaldinio at the 4th leaf, tasselling, and dent phenological stages. The transfer of carbamazepine to the aboveground and root biomass was assessed, and uptake increased dose-dependently. No direct effect on biomass production was observed, but multiple physiological and chemical changes were observed. Major effects were consistently observed at the 4th leaf phenological stage for all contamination levels, including reduced photosynthetic rate, reduced maximal and potential activity of photosystem II, decreased water potential, decreased carbohydrates (glucose and fructose) and γ -aminobutyric acid in roots, and increased maleic acid and phenylpropanoids (chlorogenic acid and its isomer, 5- O -caffeoylquinic acid) in aboveground biomass. A reduction in net photosynthesis was observed for the older phenological stages, whereas no other relevant and consistent physiological and metabolic changes related to contamination exposure were detected. Our results indicate that Z. mays can overcome the environmental stress caused by the accumulation of carbamazepine with notable metabolic changes at the early phenological stage; however, older plants adapted and only exhibited minor effects in the presence of the contaminant. The potential implications for agricultural practice could be associated with the plant's response to simultaneous stresses due to metabolite changes associated with oxidative stress. Graphical abstract: Image 1 Highlights: Carbamazepine had no effect on biomass production in maize. Carbamazepine reduced net photosynthesis in all maize phenological stages. Young maize overcame contaminant stress with metabolic changes. Older maize only displayed minor effects in the presence of the contaminant.